Relationship between quality of life of men who's wives suffer from the paranoid schizophrenia, and features its clinical-psychopathological manifestations - Maiya Driuchenko (Kazimierz Wielki University, 2016)
Driuchenko Maiya Relationship between quality of life of men who's wives suffer from the paranoid schizophrenia, and features its clinical-psychopathological manifestations. Journal of Education, Health and Sport. 2016;6(9):993-1003. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.252743 http://ojs.ukw.edu.pl/index.php/johs/article/view/4182         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7                                                                                                                                      © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 30.09.2016.   RELATIONSHIP BETWEEN QUALITY OF LIFE OF MEN WHO'S WIVES SUFFER FROM THE PARANOID SCHIZOPHRENIA, AND FEATURES ITS CLINICAL-PSYCHOPATHOLOGICAL MANIFESTATIONS   Maiya Driuchenko   Uzhgorod National University, Ukraine psychotyp@gmail.com   Summary Objective: to study the quality of life (QL) of the men whose wives suffer paranoid schizophrenia (PS). Materials and methods. On the basis of the psychiatric department of the Transcarpathian regional narcological dispensary 100 women with PS and their husbands were examined during 2014 -2016. Agroup of comparison comprised of 50 husbands of mentally health women. Results. In husbands of PS women, decline in QL in all key areas has been revealed. Most pronounced it was in the areas of psychological (emotional) well-being (index 6,04±1,66 points), self and independence in the actions (8,80±1,20 points), efficiency (8,07±1,49 points), interpersonal interaction (7,89±1,77 points) social-emotional support (8,44±1,43 points), self-realization (7,35±2,06 points) and spiritual realization (8,48 ± 1,14 points). Reduced QL of men in areas related to mental and social functioning had a close correlation with the severity of psychopathology of  their spouses. Conclusions. These data obtained formed the basis for the development of medical and psychological measures to support families of PS women. Key words: paranoid schizophrenia, women, men, quality of life.